Paul not yet justified?: the text of Philippians 3:12 in P46 - Giffin, Ryan Kristopher (TC, 2020)
The text of Phil 3:12 in P46 contains a reading in which Paul claims he has not yet been “justified” or “found righteous.” This reading, which appears in a few other witnesses (e.g., 06, 010, 012, Irenaus [Latin translation], Ambrosiaster), has been referred to as “the justification clause.” Scholars have labeled the reading “intriguing,” “very interesting,” “striking,” and “astounding.” However, scholars have devoted very little attention to this reading. This article fills that gap by highlighting the text of Phil 3:12 in P46. The author identifies four noteworthy features of the justification clause within this manuscript and proposes that the reading need not be considered “un-Pauline” (as many have understood it) but is wholly coherent with Pauline references to final justification at the last judgment. The author concludes that an early unconscious alteration due to homoioarcton or homoioteleuton best explains the absence of the reading among the majority of textual witnesses and that the justification clause should be considered authentic.